Randomized controlled trial of a home‐visiting intervention on infant cognitive development in peri‐urban South Africa. (25th August 2015) - Murray, Lynne; Cooper, Peter; Arteche, Adriane; Stein, Alan; Tomlinson, Mark
Abstract : Aim: To determine whether, in an impoverished South African community, an intervention that benefitted infant attachment also benefitted cognitive development. Method: Pregnant females were randomized to intervention ( n =220) and no‐treatment control groups ( n =229). The intervention was home‐based parenting support for attachment, delivered until 6 months postpartum. At 18 months, infants were assessed on attachment and cognitive development (Bayley Scales Mental Development Index [MDI]) ( n =127 intervention, n =136 control participants). Infant MDI was examined in relation to intervention, socio‐economic risk, antenatal depression, and infant sex and attachment. Results: Overall, there was little effect of the intervention on MDI ( p =0.094, d =0.20), but there was an interaction between intervention and risk ( p =0.03, η p 2 =0.02). MDI scores of infants of lower risk intervention group mothers were, on average, 4.84 points higher than those of other infants ( p =0.002, d =0.41). Antenatal depression was not significant once intervention and risk were controlled ( p =0.08); there was no association between infant MDI and either sex ( p =0.41) or attachment ( p =0.56). Interpretation: Parenting interventions for infant cognitive development may benefit from inclusion of specific components to support infant cognition beyond those that support attachment, and may be most effective for infants over 6 months. They may need augmentation with other input where adversity is extreme. What this paper adds: Intervention that benefits attachment might not benefit cognition. Conditions of socio‐economic adversity might limit cognitive benefits of intervention. In adverse conditions, psychological interventions for cognition may need augmentation. Cognitive interventions might be more effective with older infants. This article is commented on by Grantham‐McGregor on pages222–223 of this issue.